The definitive guide to MongoDB : a complete guide to dealing with big data using MongoDB. - Hows, David; Membrey, Peter; Plugge, Eelco; Hawkins, Tim (Tim S.) (Expert's voice in open source., 2013)
This work includes all of the latest MongoDB features, including the aggregation framework introduced in version 2.2 and hashed indexes in version 2.4.